Culturally Responsive and Sustaining Education: Implications for Christian School - Walcott, John R. (Journal of research on christian education, 2024)
Culturally responsive forms of education originally emerged from a desire to improve the educational experiences of students historically excluded and underserved by our nation’s schools. While this remains an emphasis, such forms of teaching should be desired for all students and classrooms. Therefore, it is important to consider its place in all schools. This article provides an introduction to this topic and then argues that culturally responsive and sustaining education supports the mission of Christian schools and should be an essential component of their pedagogical practice.